Comparison of Characteristics and Outcomes of Morbidly Adherent Placenta in Twin Versus Singleton Pregnancies [24L]. (May 2017) - Bateni, Zhoobin; Erfani, Hadi; Belfort, Michael; Shamshirsaz, Alireza A.
Abstract : INTRODUCTION: To compare the characteristics and outcomes of patients with morbidly adherent placenta (MAP) in twin pregnancies versus singleton pregnancies. METHODS: All patients with pathology confirmed MAP (placenta accreta, increta or percreta) from January 2000 to June 2016, were included in this retrospective study. Data were reported using descriptive statistics and appropriate statistical methods were used based on the normality of the data. RESULTS: Total of 189 cases of pathologically confirmed MAP were identified over the study period, 13 of which were twin gestations. Median gestational age at delivery, gravidity and parity were lower in twin patients (P < 0.05). Regarding the severity of the adherence, 76.9% of the twins versus 51.5% of the singletons were placenta accreta and the remainder were either placenta increta or percreta (P = 0.04). Although not statistically significant, median blood loss during the surgery was 1000 cc higher in twin pregnancies which is clinically significant. Also the median hospital stay after surgery was 2 days longer in twin gestations (P = 0.03). Moreover, the rate of unsuspected subjects in twins was higher than the singletons; 69.2% versus 27.3% (P < 0.01). CONCLUSION: As the first report comparing MAP in twin versus singleton pregnancies, our study showed higher rate of MAP in Assisted Reproductive technology and lower rate of deep invasion (i.e. placenta increta or percreta) in twins, similar to findings by others in case reports resulting from IVF. Estimated blood loss was not significantly higher, however clinically may be important.